Splice site selection in the proteolipid protein (PLP) gene transcript and primary structure of the DM-20 protein of central nervous system myelin. - Nave, K A (1987)
Proteolipid protein (PLP) is the major myelin membrane protein of the central nervous system. We have isolated a copy of an alternatively spliced PLP gene transcript from a mouse brain cDNA library that was screened for PLP-related sequences. The encoded 241-amino acid protein differs from PLP by an internal deletion of 35-amino acid residues (116-150) from the major hydrophilic domain. This PLP variant is identical with the DM-20 protein of myelin, previously described as a brain-specific myelin component and known to be related to PLP. We determined the corresponding nucleotide sequence of the rat PLP gene and found that DM-20 mRNA results when a second 5' splice site, located 105 nucleotides within the third exon of the primary PLP transcript, is utilized in precursor mRNA (pre-mRNA) splicing. This demonstrates that alternative 5' splice site selection can determine the protein product of a cellular gene. DM-20 mRNA is expressed in rat brain with approximately 50% abundance relative to PLP mRNA and appears to be developmentally coregulated.